Relationship of the use of the internet with the temperament and the academic performance in students of the third grade of secondary education in Huánuco 2014 - Rojas-Flores, Agustín R. (2019)
In this era where prevails the advance of technology and the Government is striving to implement with computer media the educational centers, with a link to the internet, this situation leaves open many possibilities as it is to determine the impact on the student in its different facets as a person. So that, the present investigation entitled" relation of the use of the internet with the temperament and the academic performance in students of the third grade of secondary education in Huánuco 2014" had as objective to determine if the use of the internet is related with the temperament and the academic performance of the student, as method the descriptive correlational design was used, and it was applied a survey and personality test, taking as sample 303 students in five educational institutions of Huánuco, the characteristics of the use of the internet in four dimensions was used; use as a means of communication, as the médium of instruction as a means of information and as a means of entertainment, the temperament type and level of academic performance of the students was determined, according to the DCN. For the contrast of hypothesis the chi square test was applied, with the following results: there is independence between the use of the Internet and the temperament, and there is no independence between the use of the Internet and the academic performance.